Bioinspired alumina/reduced graphene oxide fibrous monolithic ceramic and its fracture responses. Issue 6 (5th February 2020) - Chen, Shuna; Su, Yunfeng; Song, Junjie; Fan, Hengzhong; Jiang, Xiaofang; Hu, Litian; Zhang, Yongsheng
Abstract: Natural composites have very simple compositions and complex hierarchical architectures consisting of several different levels. These features simultaneously endow them with strength, toughness, functional adaptation, and damage‐healing characteristics. Inspired by the microstructural features of natural materials, this work successfully fabricated Al2 O3 /reduced graphene oxide (rGO) fibrous monolithic ceramics with bamboo‐like structures by introducing a thin graphene oxide around Al2 O3 fiber cells to form the rGO boundary phase. The detailed evolutions of the crack extension and fracture responses were investigated by a J‐integral method, and these bamboo‐like composites demonstrated high structural reliability with excellent damage tolerance and progressive plastic failure behavior. With the fiber cell diameter of 0.6 mm, such composites exhibited fracture toughness (29.46 ± 3.04 MPa m 1/2 ) and work of fracture (799 ± 127 J m −2 ) that were 475% and 1075% higher than those of the monolithic Al2 O3 ceramic, respectively. Their excellent fracture‐resistant behavior was attributed to the hierarchical architectures that provide crack deflection, delamination, and load redistribution. The results also established the structure‐activity relationships to guide the design and fabrication of these bamboo‐like composites.